2008
DOI: 10.1097/chi.0b013e31815cd9bc
|View full text |Cite
|
Sign up to set email alerts
|

Objective Sleep in Pediatric Anxiety Disorders and Major Depressive Disorder

Abstract: Objective-To examine objective and subjective sleep problems in early-onset anxiety and depression.Method-Children and adolescents (46% female, ages 7 to 17 years) with anxiety disorders (n = 24), major depressive disorder (MDD) without comorbid anxiety disorders (n = 128), or no history of psychiatric disorder (n = 101) spent two consecutive nights in a sleep laboratory and completed self-reports of sleep quality.Results-On objective measures, the anxiety group exhibited more awakenings than the MDD group, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
112
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 38 publications
10
112
2
Order By: Relevance
“…When examining anxiety exclusively, studies have shown that the sleep--related problems are prevalent in around 88% of youths with anxiety disorders (Alfano et al 2007). As well as studies examining subjective reports of poor sleep, findings of sleep disturbance in children with anxiety is also corroborated by studies assessing sleep using PSG as indexed by increased night--wakings and longer sleep onset latency compared to controls and those with depression (Forbes et al 2008). One study specifically focusing on generalised anxiety disorder (GAD) found increased sleep onset and REM sleep latencies in 7--11 year old children with GAD compared to controls (Alfano et al 2012).…”
Section: Sleep and Emotional Difficulties: Links Between Sleep And Emmentioning
confidence: 48%
“…When examining anxiety exclusively, studies have shown that the sleep--related problems are prevalent in around 88% of youths with anxiety disorders (Alfano et al 2007). As well as studies examining subjective reports of poor sleep, findings of sleep disturbance in children with anxiety is also corroborated by studies assessing sleep using PSG as indexed by increased night--wakings and longer sleep onset latency compared to controls and those with depression (Forbes et al 2008). One study specifically focusing on generalised anxiety disorder (GAD) found increased sleep onset and REM sleep latencies in 7--11 year old children with GAD compared to controls (Alfano et al 2012).…”
Section: Sleep and Emotional Difficulties: Links Between Sleep And Emmentioning
confidence: 48%
“…Similarly, Forbes et al [22] used EEG to assess sleep in anxiety-disordered children. Relative to those with depression and controls, anxious children displayed longer sleep latency on their second night in the laboratory.…”
Section: Sleep and Anxietymentioning
confidence: 99%
“…In particular, there is robust evidence that sleep complaints are highly prevalent among anxious youth (McMakin & Alfano, 2015;Willis & Gregory, 2015). Sleep onset and maintenance poses particular problems for children and adolescents with high levels of anxiety, possibly because their selfregulatory skills are underdeveloped compared with adults and are compromised by excessive physiologic and cognitive arousal (Alfano, Reynolds, Scott, Dahl, & Mellman, 2013;Forbes et al, 2008). Indeed, researchers have proposed a reciprocal relationship between anxiety and sleep difficulties in adolescence, whereby disturbed sleep increases vulnerability to developing anxiety, while anxiety, in turn, interferes with sleep (Dahl, 1996).…”
mentioning
confidence: 99%